Analysis of 18F-FDG uptake patterns in PET for diagnosis of septic and aseptic loosening after total hip arthroplasty - Cremerius, U.; Mumme, T.; Reinartz, P.; Wirtz, D.; Niethard, F. U.; Büll, U. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: Identification of typical patterns for fluorodeoxyglucose (FDG) uptake in positron emission tomography (PET) to detect aseptic loosening of hip prosthesis (ace-tabular and/or femoral component) and prosthetic infection. Methods: 18 patients with painful hip prosthesis underwent PET using a dedicated full ring scanner after application of 200-300 MBq FDG. The interface between bone and surrounding soft tissue or bone as displayed on coronal slices was divided into 12 segments in accordance with the classifications of Delee and Gruen. FDG uptake in each of the segments was scored (0-3) by two independent observers. Intraoperative findings were regarded as the gold standard. Results: After surgical revision 14 acetabular components and 9 femoral components were found to be loose and prosthetic infection was present in 7 prostheses. Loosening of the acetabular component was correlated to enhanced uptake in the middle of the acetabular interface, while loosening of the femoral component was correlated to enhanced uptake in the proximal and middle segment of the lateral femoral interface and the proximal segment of the medial femoral interface. A similar pattern was found in prosthetic infection with high uptake along the middle portion of the lateral fe-moral interface. In 6 of 7 infected prostheses loosening of the acetabular and of the femoral component was present. Taking the typical uptake patterns as criteria for loosening and grade 3 uptake as an additional criterion for septic loosening the accuracy of PET imaging in the detection of loosening of the acetabular or the femoral component and of prosthetic infection was 72, 78 and 89%, respectively. Conclusion: This pilot study presents FDG-PET as a promising diagnostic tool for patients with painful hip prostheses. Its clinical value should be evaluated in a larger patient population.
Keywords: Fluorodeoxyglucose; positron emission tomography; hip prosthesis; prosthetic loosening; prosthetic infection